Prevalence of burnout among healthcare workers in six public referral hospitals in northeastern Brazil during the COVID-19 pandemic: a cross-sectional study - Medeiros, Ana Irene Carlos de; Mesquita, Rafael Barreto de; Macêdo, Felipe de Souza; Matos, Antonio George de Calvacante; Pereira, Eanes Delgado (São Paulo Medical Journal, 2022)
BACKGROUND: The coronavirus disease 2019 (COVID-19) pandemic has placed considerable psychological stress on frontline healthcare workers (HCWs). OBJECTIVE: To evaluate the prevalence of burnout syndrome among HCWs facing the COVID-19 outbreak. DESIGN AND SETTING: Cross-sectional study conducted in six public intensive care units (ICUs) in the city of Fortaleza, Brazil. METHODS: An online survey was conducted among HCWs to measure the three dimensions of burnout. RESULTS: A total of 62 physicians (23.4%), 65 nurses (24.5%), 58 nurse technologists (21.9%) and 80 physiotherapists (30.2%) completed the questionnaire. Nearly half of the participants (48.6%) had high levels of emotional exhaustion, and almost one-third of them (29.4%) had high levels of depersonalization. Low levels of professional efficacy were observed in 18.1% of the sample. The independent determinants of depersonalization burnout were age < 33 years (odds ratio, OR 2.03; 95% confidence interval, CI 1.15-3.56; P = 0.01) and female gender (OR 0.33; 95% CI 0.18-0.62; P = 0.01). Increased workload was associated with both depersonalization (OR 2.37; 95% CI 2.02-5.50; P = 0.04) and emotional exhaustion (OR 1.89; 95% CI 1.04-3.58; P = 0.030). CONCLUSION: The COVID-19 pandemic has had a great impact on the dimensions of depersonalization and emotional exhaustion. Consideration of these dimensions is important when designing future burnout prevention programs for frontline personnel.